Borderwork Feminist Engagements with Comparative Literature - Higonnet, Margaret R. (Reading Women Writing, 1994)
The first book to assess the impact of feminist criticism on comparative literature, Borderwork recharts the intellectual and institutional boundaries on that discipline. The seventeen essays collected here, most published for the first time, together call for the contextualization of the study of comparative literature within the areas of discourse, culture, ideology, race, and gender. Contributors: Bella Brodzki, VèVè A. Clark, Chris Cullens, Greta Gaard, Sabine Gölz, Sarah Webster Goodwin, Margaret R. Higonnet, Marianne Hirsch, Susan Sniader Lanser, Françoise Lionnet, Fedwa Malti-Douglas, Lore Metzger, Nancy K. Miller, Obioma Nnaemakea, Rajeswari Sunder Rajan, Anca Vlasopolos.